Exploring factors associated with non-alcoholic fatty liver disease using longitudinal MRI - Friedrich Horn; Till Ittermann; Marie-Luise Kromrey; Danilo Seppelt; Henry Völzke; Jens-Peter Kühn; Felix Schön (BMC Gastroenterology, 2024)
Abstract Background To identify factors associated with non-alcoholic fatty liver disease over a 5-year period. Methods Three hundred seven participants, including 165 women, with a mean age of 55.6 ± 12.0 years underwent continuous quantitative MRI of the liver using the proton-density fat fraction (PDFF). The liver’s fat fractions were determined at baseline and 5 years later, and the frequency of participants who developed fatty liver disease and potential influencing factors were explored. Based on significant factors, a model was generated to predict the development of fatty liver disease. Results After excluding participants with pre-existing fatty liver, the baseline PDFF of 3.1 ± 0.9% (n = 190) significantly increased to 7.67 ± 3.39% within 5 years (p < 0.001). At baseline, age (OR = 1.04, p = 0.006, CI = 1.01–1.07), BMI (OR = 1.11, p = 0.041, CI = 1.01–1.23), and waist circumference (OR = 1.05, p = 0.020, CI = 1.01–1.09) were identified as risk factors. Physical activity was negatively associated (OR = 0.43, p = 0.049, CI = 0.18–0.99). In the prediction model, age, physical activity, diabetes mellitus, diastolic blood pressure, and HDL-cholesterol remained as independent variables. Combining these risk factors to predict the development of fatty liver disease revealed an AUC of 0.7434. Conclusions Within a five-year follow-up, one-quarter of participants developed fatty liver disease influenced by the triggering factors of age, diabetes mellitus, low HDL-cholesterol, and diastolic blood pressure. Increased physical activity has a protective effect on the development of fatty liver.